2004
DOI: 10.1530/eje.0.1510167
|View full text |Cite
|
Sign up to set email alerts
|

Serum parathyroid hormone level is associated with body mass index. The 5th Tromso study

Abstract: Objective: To study whether serum parathyroid hormone (PTH) and serum calcium are associated with body mass index (BMI), and their predicting role in obesity. Design: Population based, cross-sectional study. Methods:In 2001 a population-based health survey was held in Tromsø, North Norway. Questionnaires on medical history and life-style factors were completed and anthropometric data were collected. Calcium and vitamin D intakes and a physical activity score were calculated. Serum calcium and PTH were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
103
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(124 citation statements)
references
References 32 publications
16
103
2
2
Order By: Relevance
“…3,4 In addition, Kamycheva et al 23 recently demonstrated that serum levels of PTH are positively correlated with BMI in a large crosssectional study (n ¼ 7954). In this study, the relative risk of obesity was greater for those in the highest quartile of serum PTH values, independent of gender.…”
Section: Discussionmentioning
confidence: 97%
“…3,4 In addition, Kamycheva et al 23 recently demonstrated that serum levels of PTH are positively correlated with BMI in a large crosssectional study (n ¼ 7954). In this study, the relative risk of obesity was greater for those in the highest quartile of serum PTH values, independent of gender.…”
Section: Discussionmentioning
confidence: 97%
“…Obesity has been found to be associated with lower levels of serum 25-OH Vit D (1-5) and higher levels of serum PTH (1,(5)(6)(7)(8). A low vitamin D intake was associated with increased body mass index (BMI) (9).…”
Section: European Journal Of Endocrinology 157 225-232mentioning
confidence: 99%
“…A low vitamin D intake was associated with increased body mass index (BMI) (9). PTH has been postulated as an independent predictor of obesity (7). Overweight as a consequence of elevated serum PTH was explained by several mechanisms (10,11): PTH stimulates the renal hydroxylation of 25-OH Vit D to its active form, 1,25-OH Vit D, which in turn elevates the calcium influx into adipocytes.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that adiposity or related metabolic abnormalities stimulate PTH production. A number of studies have reported associations between PTH and adiposity, 5,18 as well as other cardiovascular risk factors and mortality. 19,20 Individuals with normocalcemic hyperparathyroidism have been shown to have increased BMI, triglycerides, LDL cholesterol and blood glucose.…”
Section: Discussionmentioning
confidence: 99%